Expression of microRNAs that regulate bone turnover in the serum of postmenopausal women with low bone mass and vertebral fractures. Issue 2 (February 2017) - Yavropoulou, Maria P; Anastasilakis, Athanasios D; Makras, Polyzois; Tsalikakis, Dimitrios G; Grammatiki, Maria; Yovos, John G
Abstract : Background: Circulating microRNAs (miRs) are currently being investigated as novel biomarkers for osteoporosis and osteoporotic fractures. Aim: The aim of this study was to investigate serum levels of specific microRNAs, known regulators of bone metabolism, in postmenopausal women with low bone mass and with or without vertebral fractures (VFs). Methods: For the analysis, 14 miRs were isolated from the serum of 35 postmenopausal women with low bone mass and with at least one moderate VF and 35 postmenopausal women with low bone mass without fractures. Thirty postmenopausal women with normal BMD values and no history of fractures served as controls. Main outcome parameters were changes in the expression of selected miRs in the serum of patient population and compared with controls. Results: From the 14 miRs that were selected, we identified 5 miRs, namely miR- 21-5p, miR- 23a, miR-29a-3p, miR-124-3p and miR-2861 that were significantly deregulated in the serum of patients with low bone mass compared with controls. Serum miR-124 and miR-2861 were significantly higher, whereas miR-21, miR-23 and miR-29 were lower in patients compared with controls. In a sub-group analysis of the patient population, the expression of miR-21-5p was significantly lower among osteoporotic/osteopenic women with VFs, showing 66% sensitivity and 77% specificity in distinguishing women with a vertebral fracture. Conclusion: This study identifies a differential expression pattern of miR-21-5p in the serum of women with low BMD and VFs.